PRO-KONTRA KEMUNGKINAN MELIHAT ALLAH (RU’YATULLAH) DI AKHIRAT DENGAN MATA KEPALA - Nazahah, Inayah; Sahidin, Amir (Al Jabiri: Jurnal Ilmiah Studi Islam, 2022)
In Islamic treasures, the discussion of the science of kalam has its own charm because it discusses typical Islamic thoughts, so that the Islamic building becomes stronger. One of the most important matters related to the science of kalam, is the possibility of seeing Allah (ru'yatullah) in the afterlife which reaps the pros and cons. For this reason, this article will examine the pros and cons of the possibility of seeing Allah in the hereafter by focusing on the study of the arguments or arguments used by both parties, then continue with the rebuttals. Based on the study of the type of library research with a critical analysis approach, it can be concluded. First, seeing Allah in the hereafter for Ahl sunnah wal jama'ah is a matter that must be believed by every human being who has many arguments and has reached the mutawatir level. Second, for the Mu'tazilah and those who agree with them, they do not believe that Allah can be seen in the hereafter, they postulate several verses of the Qur'an with their understanding of reason. Third, the arguments that negate this possibility are very weak and can be refuted by the experts of the sunnah wa jama'ah, so that the argument is weak, and vice versa, showing that the arguments of the Ahl sunnah wa jama'ah are stronger.